If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -3x = 4 + (y + 7) Reorder the terms: 7 + -3x = 4 + (7 + y) Remove parenthesis around (7 + y) 7 + -3x = 4 + 7 + y Combine like terms: 4 + 7 = 11 7 + -3x = 11 + y Solving 7 + -3x = 11 + y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3x = 11 + -7 + y Combine like terms: 7 + -7 = 0 0 + -3x = 11 + -7 + y -3x = 11 + -7 + y Combine like terms: 11 + -7 = 4 -3x = 4 + y Divide each side by '-3'. x = -1.333333333 + -0.3333333333y Simplifying x = -1.333333333 + -0.3333333333y
| -4x+7+7x=-20 | | -7=1/5a | | x+4-6x=-21 | | 12n+7-8n=54 | | 9w-48=-5(w+4) | | (-4x+5)-(6x+7)=0 | | 6(x+1)-3x=-9 | | -5a+2+6a=5-30 | | 5-x^2=3-x | | 2x-8/4=9 | | x^2+5x-43=7 | | -2(x-4)-12=16 | | -2(x+2)-8=10 | | 3a+6a=2a | | -5(5x+1)=45 | | 8-2(4y+12)=18 | | n-9= | | 3x*x-2=5x | | y=4x^2-9x-9 | | 3.5/.75x | | y=-3-3/5x | | y=-1/2x2-1 | | 1.07x+5=30 | | 1.7x+5=30 | | 7*6+7= | | 3.5x=.74 | | f(-6)=-3-4 | | b/13-3b/=8/13 | | W=4.2-2L/2 | | 3y=-4x+30 | | $10-3/5= | | 378t-9/7t^2 |